Mitogenic activity of Mycoplasma pulmonis. I. Stimulation of rat B and T lymphocytes. - Naot, Y (1979)
The mitogenic activity of Mycoplasma pulmonis towards both rat B and T lymphocytes has been demonstrated. The data summarized in this report show that spleen cells obtained from T X BM rats were extensively activated by M. pulmonis. Furthermore, M. pulmonis has been demonstrated to induce the development of antibody producing cells, as attested by the appearance of direct plaque forming cells against SRBC and TNP-SRBC in spleen cultures exposed to this mitogen. It was also demonstrated that rat thymus cells and a part of the lymph node T-cell population responding to either Con A or PWM, were stimulated by M. pulmonis, the response being weaker than that of rat B-cell populations. It was thus concluded that M. pulmonis activates both rat B and T lymphocytes. This mitogenic stimulation, however, is not equally exerted on both these populations, being strongly effective upon B cells and less so on T cells.